(untitled) (ETNOSIA : Jurnal Etnografi Indonesia, 2026)
Public trust in village cooperative policies is often shaped by concerns over corruption, nepotism, weak oversight, and unequal access to public resources. However, little is known about how citizens express and negotiate these concerns in short-form social media spaces such as TikTok. This article examines how TikTok users construct accountability judgments toward Indonesia’s Koperasi Desa Merah Putih (KDMP) policy. Using a qualitative netnographic approach, the study analyzes public comments on a highly viewed TikTok video posted by the verified Lingkarnews account. Of 15,500 comments, 14,782 were collected, and 10,068 meaningful comments were manually coded through open and axial coding. The analysis identified four main thematic clusters: integrity and governance, financing design, public response, and social risks. The findings show that public skepticism was the dominant response, followed by conditional support. Corruption, nepotism, loan interest, online loans, public oversight, village funds, audits, and online gambling emerged as key concerns shaping public evaluation of KDMP. These findings indicate that KDMP is judged not only by its developmental objectives but also by perceived fairness, transparency, and vulnerability to misuse. The study contributes a netnographic account of TikTok as a participatory accountability space where citizens collectively evaluate the legitimacy of rural cooperative reform through a moral economy of accountability.